ORTHODOX SPIRITUALITY AS THE ETHICAL FOUNDATION OF ALEXANDAR DESPOTOVIĆ'S TRAVEL WRITINGS (TRAVEL BOOK CENTURIES GROWN FROM ROOTS AND SYMBOL OF SVETOPOLE- SAINTFIELD) (Heritage, 2025)
Through an exhaustive analysis of the place of Orthodox spirituality as the supreme value in the poetry of Aleksandar Despotović (1933–2009), we have reaffirmed two aspects: i) to critically and fundamentally illuminate an aesthetic subject, it is necessary to read everything the writer has written and ii) once this is done, one realizes how primary the chosen theme is for understanding and evaluating the poet's work.Both truths were revealed through the travel book Centuries Grown from Roots (2000) (as an expression of the poet’s creative spirit) and A Small Orthodox Glossary (2001) (as an expression of analytical or practical action), two new forms of creative spirit that shed lateral light and follow the traces and essence of this poet of faith.In the Nemanjic’s Lavra (Monastery), Despotović, wholly devoted to prayers, once again recognizes the deepest meaning of his poetry, which he will, by fundamentally composing the Hilandar records and relying on artists and scholars, reaffirm and confirm.Despotović defines and evaluates the starting point of his path to Orthodox spirituality in his travel writing. Within a short time frame (his temporal indicators), a triptych about Kosovo Svetopole forms the central point on this narrow path, while the final one is represented by Hariton, Centuries Grown from Roots, and A Small Orthodox Glossary.
Keywords: Aleksandar Despotović, travel writing, Hilandar, poetry, Orthodox spirituality, prayer, Svetopole